Soils and plant nutrition - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
Efforts to develop cassava technology for the vast areas of acid infertile soils were continued Large-scale germplasm screening in the field was begun in Carimagua for tolerance to low levels of P and acidity and in Quilichao, for tolerance to low levels of P. Various fertilizer trials were used to determine: (a) nutrient absorption and distribution within the plant during a 12-mo. growth cycle; (b) the long-term effect of N, P, K applications on soil fertility and yield of continuously grown cassava; (c) the residual effect of various sources of P; (d) the lime x P interaction; and (e) the effect of mycorrhizal inoculation on P absorption. (CIAT)